Entomofauna asociada a pasturas tropicales Cenchrus ciliaris, Chloris gayana y Megathyrsus maximus - Sierra-Baquero, Paola Vanessa; Sánchez-Doria, Tatiana; Burbano-Erazo, Esteban (Agronomía Mesoamericana, 2023)
Introduction. Pastures are the primary source of food in livestock systems and can be a suitable niche for insects with beneficial and harmful functions. Objective. To estimate the entomofauna associated with three species of pastures, Cenchrus ciliaris, Chloris gayana, and Megathyrsus maximus, in conditions of the Colombian Caribbean. Materials and methods. Ten samplings were carried out in two contrasting periods (August to October 2018 and January to March 2019), three forage species (Cenchrus ciliaris, Megathyrsus maximus, Chloris gayana) within 1000 m2 were used. Arthropods were identified by order and family and typified by functional groups. Diversity and abundance indices by pasture and season were estimated, as well as their correlation with climate. A simple correspondence analysis was performed. Results. A total of 380 insects from 7 orders and 35 families were collected, with the greatest abundance for Hemiptera and Coleoptera. The Shannon’s diversity index was higher for all orders of C. gayana, except for Hemiptera in C. ciliaris. Phytophages were found in a higher percentage (66.84 %), followed by predators (27.11 %). Insect abundance was influenced by the interaction between season and pasture, showing an increase at low temperatures, except for M. maximus. Pastures represented adequate microenvironments to maintain the diversity of insects, the Hemiptera and Coleoptera orders being the most numerous and representative of the functional groups of phytophages and predators, respectively. Conclusion. The entomofauna of C. gayana, C. ciliaris, and M. maximus was similar in insect abundance and diversity, however, insect abundance depended on the influence of the season and pastures.